Biochemical components of Berberis lycium fruit and its effects on lipid profile in diabetic rats - Rahimi Madiseh Mohammad; Heidarian Esfandiar; Rafieian-kopaei Mahmoud (Shahrekord University of Medical Sciences, 2014)
Introduction: Diabetes mellitus is characterized by chronic hyperglycemia with disturbances of carbohydrate, fat, and lipid metabolism resulting from defect in insulin secretion, insulin action, or both. It not only leads to hyperglycemia but also may cause hyperlipidemia. Herbal medicines have always been considered as a healthy source of life. Although medicinal herbs and their derivatives have long been used for hyperlipidemia, their definite effects have not yet been proven by valid research. The aim of this study was to measure minerals in B. lycium fruit and to evaluate the effects of its ethanolic extract on lipid profile in diabetic rats. Methods: For this study 40 male Wistar rats were used and were divided into five equal groups. For induction of diabetes in animals, alloxan monohydrate was used. The animals were under treatment for 42 days. For healthy and diabetic control groups distilled water, for positive diabetic control metformin, for the fourth and fifth diabetic groups Berberis lycium extract in respectively 200 and 600 mg/kg dose were used, daily. Blood samples were collected from heart and lipid profile was measured with autoanalyzer and HPLC. Results: The results of the study indicated that iron level in Berberis lycium fruit was considerably high. In diabetic rats administered with Berberis lycium fruit extract in 600 mg/kg dose, the lipid profile decreased significantly (p<0.05). Conclusion: The present investigation showed that the Berberis lycium fruit extract alleviates lipid profile level and might be used efficiently in hyperlipidemia, especially in diabetic patients. It may also be beneficial in iron deficiency.